Kinerja Panel Surya Apung Pada Kulong Pasca Tambang Timah - Rika Favoria Gusa; M. Yonggi Puriza; Yuant Tiandho; Wahri Sunanda (JURNAL NASIONAL TEKNIK ELEKTRO, 2019)
Tin mining in the Bangka Belitung Islands Province, leaving a basin called the kulong. Kulong has an irregular landscape and contains very small amount of nutrients. Basically, kulong can be a storage place for water reserves to support the fisheries sector. But often, kulong water has poor dissolved oxygen concentration so that it is not suitable for fish growth. Therefore it needs an aeration system that can supply oxygen. The development of integrated aeration technology with floating solar panels in the kulong area is an interesting alternative solution to be developed. The floating solar panel system consists of a 50 Wp solar panel which is floated on a rectangular 4” PVC pipe and connected to a solar charge controller (MPPT), sealed lead-acid battery 12V 12 Ah and a 12V DC aerator as a source of aeration. An aluminum heatsink is installed at the bottom of the solar panel to transfer heat from solar panel to the kulong water so that temperature gets drop and the solar panel can produce higher voltage than solar panel placed on land. The voltage of the floating solar panel with the heatsink is higher on average 0.41V so that the average power generated by the floating solar panel is also about 2% higher than the power generated by solar panel on land.Key Words: Floating Solar Panel, Tin Kulong and AerationAbstrakPenambangan timah di Provinsi Kepulauan Bangka Belitung menyisakan cekungan yang disebut dengan kulong. Kulong memiliki lanskap yang tidak beraturan serta hanya mengandung unsur hara dalam jumlah yang sangat kecil. Pada dasarnya kulong dapat menjadi tempat penyimpanan cadangan air untuk mendukung sektor perikanan. Tetapi seringkali air kulong memiliki kadar konsentrasi oksigen terlarut yang buruk sehingga tidak baik bagi pertumbuhan ikan. Oleh karena itu dibutuhkan sistem aerasi yang dapat menyuplai oksigen. Pengembangan teknologi aerasi yang terintegrasi dengan panel surya apung di area kulong adalah solusi alternatif yang menarik untuk dikembangkan. Sistem panel surya apung terdiri dari panel surya 50 Wp yang diapungkan di atas pipa PVC 4” berbentuk persegi panjang dan dihubungkan dengan solar charge controller (MPPT), sealed lead-acid battery 12V 12 Ah dan aerator 12V DC sebagai sumber aerasi. Heatsink berbahan aluminium dipasang di bawah panel surya untuk mengalirkan panas dari panel surya ke air kulong sehingga suhu turun dan dapat menghasilkan tegangan lebih tinggi daripada panel yang diletakkan di darat. Tegangan panel surya apung dengan heatsink lebih tinggi rata-rata 0,41V sehingga rata-rata daya yang dibangkitkan oleh panel surya apung juga lebih tinggi sekitar 2% dibandingkan dengan daya yang dihasilkan oleh panel surya di darat.Kata Kunci : Panel Surya Apung, Kulong Timah dan Aerasi